EVALUASI PENINGKATAN KENYAMANAN TERMAL RUMAH TINGGAL MELALUI IMPROVEMENT MATERIAL SELUBUNG BANGUNAN DI KOTA MAKASSAR - Nurhayati Kamaruddin; Nurhasanah H; Muh. Rahmansyah Alfian (Program Vokasi Universitas Negeri Gorontalo, 2026)
Thermal comfort is an important aspect of residential building design in tropical regions such as Makassar City. This study aims to analyze the effect of material improvement on the thermal performance of a two-story residential building using Autodesk Ecotect Analysis 2011. The analyzed parameters include Mean Radiant Temperature (MRT), Predicted Mean Vote (PMV), Hourly Temperature Profile, Internal Gains, and Direct Solar Gains. Material improvement was conducted by replacing Brick Plaster walls with Brick Cavity Concrete Block Plaster and Single Glazed Timber Frame windows with Double Glazed Low-E Timber Frame. The simulation results indicate that the existing building did not meet thermal comfort criteria, with MRT values ranging from 32–39°C on the first floor and 29–34°C on the second floor, while PMV values were generally above +3. The master bedroom recorded the highest Direct Solar Gains value of 284 Wh and a maximum indoor temperature of 32.5°C. After the material improvement, indoor temperatures decreased by 0.9–1.3°C. The findings demonstrate that building envelope materials with better thermal performance can reduce heat transfer into the building and improve indoor thermal conditions.